Beyond the Social Contract: Power, Right, and State in Spinoza’s Political Philosophy - Hoefling, Simon (Colloquium: The Political Science Journal of Boston College, 2025)
This paper examines Baruch Spinoza’s political theory and its evolution from the Theologico-Political Treatise to the Political Treatise. Spinoza’s mature political philosophy rejects the notion of a voluntary transfer of power central to Hobbesian contractualism, instead grounding political authority in power relations and the passions. By exploring Spinoza’s metaphysical stance on power and natural right, the paper contrasts his ideas with Hobbes, arguing that civil society is a natural extension of human interaction instead of a rational, contractual agreement. Ultimately, Spinoza’s theory offers a compelling philosophical alternative to traditional social contract frameworks.